Consulates under diplomatic pressure? Bureaucratic resistance and relational discretion in visa issuance in China - Juliette Dupont (Political Research Exchange)
This study examines the intricate dynamics of visa policy implementation, focusing on the conflicting imperatives of promoting tourism and ensuring border security. Through ethnographic immersion within a visa service abroad and interviews with consular and diplomatic staff, the research reveals the struggles between competing street-level actors. The article argues that visa officers exercising discretion are embedded within a web of relationships that include both rival and allied actors. These officers leverage their bureaucratic autonomy to resist an attractiveness policy they perceive as inconsistent with the primary function of the visa, while relying on the immigration liaison officer to reinforce a policing approach of border control. By highlighting the relational and interdependent nature of visa policy, the findings contribute to a broader understanding of the openness versus closure dilemma faced by immigration frontline workers.